Comparison of Sound Absorption Coefficient for Natural Fiber - ABDUL AZIZ, MUHAMMAD AFHAM; Mohd Sari, Kamarul Aini (Progress in Engineering Application and Technology, 2021)
The application of acoustic panels is one of the most important methods for sound insulation in buildings. Moreover, sound absorption materials for sound control are distinguished due to their high efficiency in sound absorption. Most materials are synthetic and cannot be disposed of as solid waste in nature or burned by industry, as they are highly polluting. The aims of this study to evaluate the sound absorption coefficient of four natural fibers: kenaf, chicken feather, coconut and sugarcane. Ten articles was reviewed focused on density, thickness (20, 30 and 40 mm) and Sound Absorption Coefficient (SAC) at low frequency (2000 Hz). The results for four natural fibers found that SAC of 0.90, 0.79, 0.66 and 0.59 at 2000Hz frequency. However, the increase in frequency rate of 250Hz to 2000Hz shows that kenaf fiber and coconut fiber alone are always increasing for the level of sound absorption. Meanwhile the density for three natural fibers increase namely kenaf fiber, chicken feathers and sugarcane with 837.5kg/m3, 790kg/m3 and 730kg/m3 at 40% weight of natural materials proportion. Regarding the thickness of natural fibers that has been selected give an important role that sound absorption in porous materials has a direct relationship with thickness at low frequency by having a thickness of 10mm to 40mm for acoustic panels. In conclusion, kenaf fiber proved to have good sound absorption performance in normal and random occurrence sound absorption while applied for building materials.